SOME BIOLOGICAL PARAMETERS OF THE NILE TILAPIA, OREOCHROMIS NILOTICUS L. 1758, FROM ATBARA RIVER AND KHASHM EL-GIRBA RESERVOIR, EASTERN SUDAN - Abdalla, Mutasim Yousif Mohamed; Abdelhalim, Abuelgasim Ibrahim; Alawad, Abdalla N.; Shuaib, Mujtaba El-Khair; Elhassan, Moatez Mohammed (JFMR (Journal of Fisheries and Marine Research), 2023)
This study aimed to investigate the abundance, length-weight relationship, and condition factor of Oreochromis niloticus (L. 1758) in the Khashm El-Girba reservoir and Atbara River. The survey was conducted from December 2015 to November 2016. Samples were collected bi-monthly from three sites: Um Aswad (Atbara River), El-Remila, and El-Monaba (The reservoir), using seine beach nets of 1.2, 4, and 7 cm stretched bar mesh. A total of 1595 O. niloticus specimens were collected from all sampling sites. Out of the total catch, O. niloticus was found dominant in the Khashm El-Girba reservoir. It contributed 25.67% and 19.12% El-Remila and El-Monaba, respectively, and represented 15.13% at Um Aswad (Atbara River). This study indicates two increase periods of abundance for O. niloticus in the upper stream and only one increase of abundance downstream. The length-weight relationship of O. niloticus species indicates that the allometric growth pattern b value fluctuated between 2.78 and 2.96. The mean condition factor of O. niloticus ranged between 2.55 to 3.56.